APPROACHES TO THE DEVELOPMENT OF INTERACTIVE ELECTRONIC TEXTBOOKS AND TEACHING MATERIALS IN ANALYTICAL CHEMISTRY - Велика, Алла; Кропельницька, Юлія; Гарвасюк, Олександра (SWorldJournal, 2025)
The authors of the article discuss current approaches to the development of electronic teaching materials for studying analytical chemistry. Key principles of didactic design, technical aspects of creating interactive content, as well as the possibilities